The Effect of Performance Expectancy and Effort Expectancy on Purchase Intention in Wuling Electric Cars in the City of Bandung - Aldi Setiawan; Abdul Ahmad Hafidh Nurmansyah (LP2M IAIN Palopo, 2026)
This study examines the effects of performance expectancy and effort expectancy on purchase intention toward Wuling electric cars in Bandung City. Methods: A quantitative explanatory survey used purposive sampling among 134 Bandung residents aged at least 17 years who were familiar with Wuling electric cars. Twelve indicators were measured on a five-point Likert scale and analyzed using multiple linear regression in SPSS. Results: Performance expectancy positively affected purchase intention (B = .448; β = .550; t(131) = 9.694; p < .001), as did effort expectancy (B = .391; β = .541; t(131) = 9.537; p < .001). Jointly, both predictors were significant, F(2, 131) = 89.886, p < .001, and explained 57.8% of purchase intention variance. Implications: Wuling should emphasize measurable performance benefits and reduce perceived complexity through demonstrations, charging guidance, and accessible after-sales support. The study extends UTAUT to brand-specific electric vehicle purchase intention in an Indonesian urban market.